Measuring the Role of Zakat in the Development of HDI with a License Approach (Case Study of BAZNAS Bekasi City) - Wahyudi, Dikky; Ismail, Nurizal; Al-Ayubi, Solahuddin (University of Darusssalam Gontor, 2024)
This research creates a breakthrough by bringing the National Zakat Index (IZN) approach to measure the role of zakat in increasing the Human Development Index (HDI), an aspect that is still minimally explored in the literature. Focusing on analyzing the performance of BAZNAS Bekasi city provides added value, considering that BAZNAS Bekasi city has proven to be good and transparent in the distribution of Zakat, Infaq, and Shadaqah (ZIS) funds. This research aims to measure the role of zakat in increasing the Human Development Index (HDI) in Bekasi city. The research method used was a mixed method, where data was collected through interviews and questionnaires. The sample selection process was carried out randomly using a simple random sampling technique, and data analysis was carried out using the National Zakat Index (IZN) approach. The findings in this research indicate that the role of zakat in increasing the human development index in Bekasi city has a significant impact, with the micro dimension index value reaching around 84%. Apart from that, zakat also has a significant influence on the welfare and independence index of the community in Bekasi city.